Kinerja Pengaruh Marketing Mix Terhadap Keputusan Pembelian Konsumen Produk Kerajinan Batu Alam (Gemstone) Di Kecamatan Patrang Jember - Amien Pudjanarso; Hayatul Maspufah (RELASI : JURNAL EKONOMI, 2019)
Marketing mix consisting of a variable product, price, place, and promotion. This study aimed (1) to determine the effect of product variables (X1), price(X2), place (X3), and promotion (X4) on consumer purchasing decisions (Y) UKM Jamal Gemstone simultaneously or partially. (2) To determine which variables are the most dominant on consumer purchasing decisions UKM Jamal Gemstone. By using descriptive and analytical methods. The analytical tool used in this study are as follows : (1). classical assumption ( normality test, multicolinearity test, heterokedastisitas test), (2). Hypothesis testing ( Multiple Linier Regression Analysis, test F, test t, Analysis Of The Coefficient Of Determination (R2 )). The results of the study showed that all marketing mix variables (independent) positif and significant impact on consumer purchasing decisions (dependent). Results of F count of 65,872 with a significance level 0,000 < 0,05 supported test results of determination (R2 ) of 0,724 this means it has been explained that the marketing mix 72,4% influence the consumer’s decision 27,6% influence by other variables. The results of the test t variables that influence the price.